2018
DOI: 10.1007/s11661-018-4567-6
|View full text |Cite
|
Sign up to set email alerts
|

Segregation-Assisted Plasticity in Ni-Based Superalloys

Abstract: Correlative high-resolution transmission electron microscopy and energy-dispersive X-ray spectroscopy are used to study deformation-induced planar faults in the single-crystal superalloy MD2 crept at 800°C and 650 MPa. Segregation of Cr and Co at microtwins, anti-phase boundaries (APB), and complex/superlattice extrinsic and intrinsic stacking faults (CESF/SESF and CISF/SISF) is confirmed and quantified. The extent of this is found to depend upon the fault type, being most pronounced for the APB. The CESF/SESF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 38 publications
7
30
0
Order By: Relevance
“…This provides a new pathway for control of fault energies and higher length scale mechanical properties sensitive to this property. Similar phenomena have also been observed in commercial nickel-based superalloys, 59,60 suggesting new strategies for alloying in both classes of materials. This approach to tailoring of interface properties promises improved fracture properties, control of grain growth, and stabilization of nanocrystalline structures.…”
Section: Resolutionsupporting
confidence: 68%
See 1 more Smart Citation
“…This provides a new pathway for control of fault energies and higher length scale mechanical properties sensitive to this property. Similar phenomena have also been observed in commercial nickel-based superalloys, 59,60 suggesting new strategies for alloying in both classes of materials. This approach to tailoring of interface properties promises improved fracture properties, control of grain growth, and stabilization of nanocrystalline structures.…”
Section: Resolutionsupporting
confidence: 68%
“…This has enabled, for example, rigorous studies of segregation to grain boundaries and stacking faults. [57][58][59][60][61][62][63][64][65][66][67][68] Refractory element segregation has been observed at superlattice intrinsic stacking faults in a new class of cobalt-based alloys containing L1 2 precipitates, 57,58,69,70 and is revealed by both local electrode atom probe tomography and high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) (see Figure 3a). This provides a new pathway for control of fault energies and higher length scale mechanical properties sensitive to this property.…”
Section: Resolutionmentioning
confidence: 99%
“…Stacking faults are formed due to a thermally activated reaction of a/2<110>{111} dislocations, which results in a leading partial dislocation of a/3<112> type creating a superlattice intrinsic stacking fault (SISF) and a trailing partial dislocation of a/6<112> type that remains at the / interface. Additionally, it is known that segregation of solutes to planar faults influences the defect energies and their formation process significantly [26,[29][30][31][32]. Furthermore, local diffusive reordering processes occur and defect arrangements can be changed driven by an energy reduction [30,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…[40] Recent studies have identified diffusion-activated plasticity as an additional operating mechanism which could explain the decreasing strength in this temperature regime. [41,42] A further significant weakening effect at higher temperatures is a decrease in c 0 volume fraction, / p . Calculations using Thermo-Calc and the TTNi8 Ni-alloy database predict a decrease from 58 pct at 600°C to nearly 0 pct at 1150°C (see Figure 13(d)).…”
Section: B Stepped-temperature Testsmentioning
confidence: 99%